ESTIMATION OF REGIONAL INNOVATION ACTIVITY - Arzu Huseynova; Ophelya Mazanova (Agora International Journal of Economical Sciences (AIJES), 2023)
In the article, the estimation of the regional innovation activity, the general methodology of the estimation of the innovation development of the regions in this direction were analyzed by the author. The innovation index was formed based on the principles accepted in the international world to assess the innovation potential. According to the comparative evaluation of Azerbaijan's innovation potential, an innovation index was found for each region, zones were ranked according to this index, and cluster analysis was conducted. The selected system of indicators allows us to evaluate the level of innovation development in different areas, and to analyze the factors affecting the innovation index in the regions.
Keywords: 330